PERAN POLA ASUH BERBASIS KEARIFAN LOKAL DALAM MENDUKUNG STATUS GIZI BALITA DI KOMUNITAS PEDESAAN - Ristamaya Danar Dewi; Wiqodatul Ummah (ASSYIFA : Jurnal Ilmu Kesehatan, 2026)
Nutritional problems among children under five remain a major public health concern in Indonesia, including both undernutrition and the increasing prevalence of overweight and obesity in early childhood. Parenting practices influenced by local wisdom are still widely applied in rural communities and may affect children’s dietary patterns and nutritional outcomes. This study aimed to analyze the role of local wisdom-based parenting practices in supporting the nutritional status of children under five in rural communities. This study employed a quantitative approach with a cross-sectional design. The research was conducted in Sumbersekar Village, Dau District, Malang Regency, from November 2025 to February 2026. A total of 34 mothers with children aged 6-59 months were selected using stratified random sampling. Data were collected through structured questionnaires assessing local wisdom-based parenting practices and anthropometric measurements to determine children’s nutritional status. Data were analyzed using descriptive statistics, Chi-square tests, and multinomial logistic regression. The results showed that most respondents applied local wisdom-based parenting practices in the good category (55.9%). The majority of children had normal nutritional status (61.8%), while 14.7% were undernourished, 17.6% were overweight, and 5.9% were obese. Statistical analysis indicated a significant association between local wisdom-based parenting practices and children’s nutritional status (p = 0.032). In conclusion, local wisdom-based parenting practices play an important role in determining children’s nutritional status. Integrating cultural values with balanced nutrition education may improve healthy feeding practices in rural communities.